A phase I study of pulse high‐dose vorinostat (V) plus rituximab (R), ifosphamide, carboplatin, and etoposide (ICE) in patients with relapsed lymphoma. (29th January 2013) - Budde, Lihua E.; Zhang, Michelle M.; Shustov, Andrei R.; Pagel, John M.; Gooley, Ted A.; Oliveira, George R.; Chen, Tara L.; Knudsen, Nancy L.; Roden, Jennifer E.; Kammerer, Britt E.; Frayo, Shani L.; Warr, Thomas A.; et al.
Summary: Given the poor outcomes of relapsed aggressive lymphomas and preclinical data suggesting that ≥2·5 μmol/l concentrations of vorinostat synergize with both etoposide and platinums, we hypothesized that pulse high‐dose vorinostat could safely augment the anti‐tumour activity of (R)ICE [(rituximab), ifosphamide, carboplatin, etoposide] chemotherapy. We conducted a phase I dose escalation study using a schedule with oral vorinostat ranging from 400 mg/d to 700 mg bid for 5 d in combination with the standard (R)ICE regimen (days 3, 4 and 5). Twenty‐nine patients [median age 56 years, median 2 prior therapies, 14 chemoresistant (of 27 evaluable), 2 prior transplants] were enrolled and treated. The maximally tolerated vorinostat dose was defined as 500 mg twice daily × 5 d. Common dose limiting toxicities included infection ( n = 2), hypokalaemia ( n = 2), and transaminitis ( n = 2). Grade 3 related gastrointestinal toxicity was seen in 9 patients. The median vorinostat concentration on day 3 was 4·5 μmol/l (range 4·2–6·0 μmol/l) and in vitro data confirmed the augmented antitumour and histone acetylation activity at these levels. Responses were observed in 19 of 27 evaluable patients (70%) including 8 complete response/unconfirmed complete response. High‐dose vorinostat can be delivered safely with (R)ICE, achieves potentially synergistic drug levels, and warrants further study, although adequate gastrointestinal prophylaxis is warranted.